Zderzenie codzienności XIX–XXI wieku w powieści »Prsten od vévodkyně« Františka Novotnego - Pająk, Aleksandra (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2014)
The paper entitled ‘Clash of the reality from the XIX and XXI century in František Novotný’s novel Prsten of vévodkyně’ attempts to show the strategies that the author uses reconstructing distant and recent past. The book is the first part from the series Kroniky karmínových kamenů, which aims to approach Czech history in a different way than it is presented in school textbooks. The author offers the reader two almost parallel stories. The character of this „new” history is an ex-secret service agent - Zdeněk Milbach, who travels through Czech history using the time machine (which is the portrait of Božena Němcová). There is also a story from the past describing the life of his ancestor Mühlbach. He similarly is a police secret agent who is following Němcová, just like Milbach is following Alena Michálkova. It that way, Novotný proves that despite of the fact that the XIX century is already ‘historical’ period, it has a lot in common with recent history. In both periods the author stresses the events from the years 1848 and 1989, which, all the same, are milestones in the lives of both characters. This piece of work, that constitutes as hybrid combination of detective story and historical fantasy, is the example of revitalization of the subject of history in contemporary literature.
Keywords: historical prose; XIX century history; modern experience; František Novotný; Božena Němcová